Light conversion adhesive film, preparation method thereof and photovoltaic module
By using a multi-layered light-to-adhesive film in photovoltaic modules to convert and optimize the light frequency band, the problem of low utilization of photovoltaic modules for different light frequency bands is solved, and higher power gain and life extension is achieved.
Patent Information
- Application Number
- CN202411307322.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-13
AI Technical Summary
The utilization rate of existing photovoltaic modules on ultraviolet, blue light and infrared light is low, resulting in a decrease in power performance and life, and there are problems of mutual interference and low utilization rate between light rays in different frequency bands.
The light-to-converting film adopts a multi-layer structure, including a first light-to-converting layer, a second light-to-converting layer, a diffuse reflecting layer and a light-guiding layer, is prepared by coextrusion and thermal bonding technology, the first light-to-converting layer and the second The light-to-transformation layer converts ultraviolet light into blue and green light respectively, and improves the diffuse reflection and transmittance of light through the diffuse reflective layer and the light guide layer.
The utilization rate of photovoltaic modules for light in various frequency bands is significantly improved, the overall power gain is improved, the power attenuation of photovoltaic modules is reduced, and the cut-off utilization rate of ultraviolet rays is improved.
Smart Images

Figure CN119119901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photovoltaic technology, and in particular to a light-transfer adhesive film and a preparation method thereof, and a photovoltaic module. Background Art
[0002] With the application of technologies such as cell microcrystallization, thinning and surface laser sintering, cells are increasingly affected by ultraviolet light, blue light and infrared light, which have a great impact on the power performance and life of photovoltaic modules. Among them, ultraviolet light will affect the microcrystallization layer on the surface of the cell, affecting the carrier transmission process; infrared light can penetrate the glass cover of the photovoltaic module and reach the surface of the cell, generating a thermal effect that causes the cell temperature to rise, reducing the output power and efficiency of the photovoltaic module; on the other hand, although blue light can be effectively absorbed and utilized by the battery as a light that can be absorbed and utilized by the module, it will be offset due to its proximity to the ultraviolet light band, resulting in insufficient utilization.
[0003] The utilization of ultraviolet light, blue light and green light at the module end is one of the important factors affecting system performance. At present, the utilization rate of the three frequency bands of light at the module end is low, and there is mutual interference between the various lights, which leads to a significant reduction in the utilization efficiency of light by the entire photovoltaic module system.
[0004] Existing photovoltaic modules cannot take into account the utilization of light in various frequency bands. The main reasons are as follows:
[0005] (1) The light conversion aids in different frequency bands will affect each other due to the interaction between frequency bands, thereby reducing the light response between different frequency bands. For example, in the process of converting ultraviolet light to blue light or red light, since the battery's response to blue light is slightly higher than that to red light, the same light beam will be insufficiently utilized if it is excited by both ultraviolet light and infrared light.
[0006] (2) Light waves cannot achieve diffuse reflection.
[0007] (3) At present, power enhancement mostly relies on a single method, for example, using ultraviolet light conversion powder in the encapsulation film to convert ultraviolet light into blue light, and increasing the amount of blue light to improve the utilization rate of blue light by the component; or converting ultraviolet light into red light to improve the utilization rate of red light by the component and thus improve the power of the component. Moreover, the power gain effect generated by the above light utilization is also affected by many factors, such as light angle, ambient temperature, cell type, etc.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] One object of the present invention is to provide a light transfer adhesive film that can improve the utilization rate of light in various frequency bands by photovoltaic modules, thereby improving the power gain of the entire module.
[0010] Another object of the present invention is to provide a method for preparing the optical transfer adhesive film.
[0011] Another object of the present invention is to provide a photovoltaic module, comprising the above-mentioned light transfer adhesive film.
[0012] In order to achieve the above-mentioned object of the present invention, the present invention provides a light transfer adhesive film on one hand, comprising a first light transfer layer, a second light transfer layer, a diffuse reflection layer and a light guide layer arranged in sequence;
[0013] The first light conversion layer is mainly made of 100 parts by weight of a first base resin, 0.3-0.9 parts of an initiator, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer, and 0.3-0.8 parts of a first light conversion powder;
[0014] The second light conversion layer is mainly made of 100 parts by weight of a second base resin, 0.3-0.7 parts of an initiator, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer, and 0.3-0.8 parts of a second light conversion powder;
[0015] The first light conversion powder receives light with a wavelength of 280 to 320 nm and converts it to generate blue light; the second light conversion powder receives light with a wavelength of 320 to 400 nm and converts it to generate green light.
[0016] In a specific embodiment of the present invention, the first light conversion powder is mainly prepared from benzotriazole compounds, magnesium oxide, ethylene-methyl acrylate copolymer and diffuse reflection powder in a mass ratio of 1:(0.5-0.8):(1.5-2):(0.6-1).
[0017] In a specific embodiment of the present invention, the second light conversion powder is mainly made of fluorescent powder, benzotriazole compound, magnesium oxide, ethylene-methyl acrylate copolymer and diffuse reflection powder in a mass ratio of (1.1-1.3) ﹕ 1 ﹕ (0.5-0.8) ﹕ (1.5-2) ﹕ (0.6-1).
[0018] In a specific embodiment of the present invention, the phosphor includes sodium yttrium tungstate crystals.
[0019] In a specific embodiment of the present invention, the structural formula of the benzotriazole compound is as follows:
[0020]
[0021] In a specific embodiment of the present invention, the diffuse reflection layer is mainly prepared by weight portions of 100 parts of a third base resin, 0.3 to 0.9 parts of an initiator, 0.1 to 5 parts of a silane coupling agent, 0.6 to 1 parts of an acrylate monomer, 0.1 to 0.15 parts of an antioxidant, 0.05 to 0.09 parts of a light stabilizer and 10 to 15 parts of a diffuse reflection powder.
[0022] In a specific embodiment of the present invention, the light-guiding layer is mainly prepared by weight portions of 75-85 parts of a fourth matrix resin, 0.3-0.9 parts of an initiator, 15-25 parts of a light-guiding masterbatch, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer and 8-16 parts of a diffuse reflection powder.
[0023] In a specific embodiment of the present invention, the longitudinal section of the light guide layer includes a plurality of isosceles triangles evenly arranged in the horizontal direction;
[0024] The length of the base and the height of the isosceles triangle are 10-15 μm and 80-120 μm respectively; the distance between the centers of adjacent isosceles triangles is 14-20 μm.
[0025] In a specific embodiment of the present invention, the vertex of the isosceles triangle faces the diffuse reflection layer.
[0026] In a specific embodiment of the present invention, the first matrix resin and the second matrix resin each independently include at least one of ethylene-vinyl acetate copolymer and ethylene-acrylic acid copolymer. Further, in the first matrix resin and the second matrix, the mass ratio of the ethylene-vinyl acetate copolymer to the ethylene-acrylic acid copolymer is (3-5):1;
[0027] In a specific embodiment of the present invention, the third matrix resin is ethylene-vinyl acetate copolymer.
[0028] In a specific embodiment of the present invention, the fourth matrix resin includes at least one of ethylene-vinyl acetate copolymer and ethylene-methyl acrylate copolymer. Further, in the fourth matrix resin, the mass ratio of the ethylene-vinyl acetate copolymer to the ethylene-methyl acrylate copolymer is (6-8) : 1;
[0029] In a specific embodiment of the present invention, the light-guiding masterbatch is mainly made of a matrix and a diffuse reflective powder in a mass ratio of (3.5-4.5) : 1. Furthermore, the matrix is an ethylene-methyl acrylate copolymer.
[0030] In a specific embodiment of the present invention, in the optical transfer adhesive film, the thickness of the first optical transfer layer is 130-150 μm, the thickness of the second optical transfer layer is 110-130 μm, and the total thickness of the diffuse reflection layer and the light guide layer is 280-320 μm.
[0031] Another aspect of the present invention provides a method for preparing any one of the above-mentioned light transfer adhesive films, comprising the following steps:
[0032] (a) co-extruding the first light conversion layer and the second light conversion layer according to the raw material ratio to obtain a light conversion composite layer;
[0033] (b) co-extruding the diffuse reflection layer and the light guide layer according to the raw material ratio, and performing heat bonding treatment with the light conversion composite layer, and winding;
[0034] During the thermal bonding process, the second light conversion layer of the light conversion composite layer is bonded to the diffuse reflection layer.
[0035] Another aspect of the present invention provides a photovoltaic module, comprising any one of the above-mentioned light transfer adhesive films.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The light-converting adhesive film of the present invention can convert ultraviolet light into blue light and green light through a multi-layer structure, and improve the diffuse reflection of the converted blue light and green light. At the same time, the diffuse reflection layer and the light guide layer are used in combination to improve the transmittance and utilization rate of the converted blue-green light;
[0038] (2) The photovoltaic module made by using the encapsulation film of the present invention can significantly improve the utilization rate of light in each frequency band, thereby improving the power gain of the overall module. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 A schematic diagram of the structure of a light transfer adhesive film provided in an embodiment of the present invention;
[0041] Figure 2 A schematic diagram of a partially enlarged structure of a longitudinal section of a diffuse reflection layer and a light guide layer provided in an embodiment of the present invention;
[0042] Figure 3A schematic diagram of the structure of a single-module co-extrusion die head provided in an embodiment of the present invention;
[0043] Figure 4 A schematic diagram of the positional relationship between the light guide layer and the main grid lines of the optical transfer adhesive film provided in an embodiment of the present invention.
[0044] Reference numerals:
[0045] 1-first light conversion layer; 2-second light conversion layer; 3-diffuse reflection layer;
[0046] 4-light guide layer; 5-cell; 6-gate line. DETAILED DESCRIPTION
[0047] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0048] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0049] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0050] Figure 1 The structure diagram of the optical transfer adhesive film provided by the embodiment of the present invention is shown in FIG. Figure 1It can be seen that the light transfer adhesive film includes a first light transfer layer 1, a second light transfer layer 2, a diffuse reflection layer 3 and a light guide layer 4 which are arranged in sequence.
[0051] Among them, the first light conversion layer 1 is mainly prepared by 100 parts of the first base resin, 0.3-0.9 parts of the initiator, 0.1-5 parts of the silane coupling agent, 0.6-1 parts of the acrylate monomer, 0.1-0.15 parts of the antioxidant, 0.05-0.09 parts of the light stabilizer and 0.3-0.8 parts of the first light conversion powder.
[0052] For example, in different embodiments, in the first light conversion layer 1, by weight, compared to 100 parts of the first matrix resin, the amounts of the remaining components may be as follows:
[0053] The amount of the initiator can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.9 parts or a range consisting of any two of them;
[0054] The amount of the silane coupling agent can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or a range consisting of any two of them;
[0055] The amount of the acrylic acid ester monomer can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part or a range consisting of any two of them;
[0056] The amount of the antioxidant can be 0.1 part, 0.11 part, 0.12 part, 0.13 part, 0.14 part, 0.15 part or a range consisting of any two of them;
[0057] The amount of the light stabilizer can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or a range consisting of any two of them;
[0058] The dosage of the first light conversion powder can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or a range consisting of any two of them; the first light conversion powder receives light with a wavelength of 280 to 320 nm and converts it to produce blue light.
[0059] The first light conversion layer 1 of the present invention has a strong response to ultraviolet light in the 280-320 nm band and can convert ultraviolet light into blue light.
[0060] The second light conversion layer 2 is mainly prepared by weight from 100 parts of a second base resin, 0.3-0.7 parts of an initiator, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer and 0.3-0.8 parts of a second light conversion powder.
[0061] For example, in different embodiments, in the second light conversion layer 2, by weight, compared to 100 parts of the first matrix resin, the amounts of the remaining components may be as follows:
[0062] The amount of the initiator can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or a range consisting of any two of them;
[0063] The amount of the silane coupling agent can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or a range consisting of any two of them;
[0064] The amount of the acrylic acid ester monomer can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part or a range consisting of any two of them;
[0065] The amount of the antioxidant can be 0.1 part, 0.11 part, 0.12 part, 0.13 part, 0.14 part, 0.15 part or a range consisting of any two of them;
[0066] The amount of the light stabilizer can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or a range consisting of any two of them;
[0067] The dosage of the second light conversion powder can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or a range consisting of any two of them; the second light conversion powder receives light with a wavelength of 320 to 400 nm and converts it to produce green light.
[0068] The second light conversion layer 2 of the present invention has a strong response to ultraviolet light in the 320-400nm band and can convert ultraviolet light into green light.
[0069] In a specific embodiment of the present invention, the first light conversion powder is mainly prepared from benzotriazole compounds, magnesium oxide, ethylene-methyl acrylate copolymer and diffuse reflection powder in a mass ratio of 1:(0.5-0.8):(1.5-2):(0.6-1).
[0070] By compounding the above substances in the first light conversion powder, the diffuse reflection of the converted light can be improved while ensuring the conversion of ultraviolet light.
[0071] For example, in different embodiments, in the first light-conversion powder, the mass ratio of magnesium oxide to benzotriazole compounds can be 0.5:1, 0.6:1, 0.7:1, 0.8:1 or a range consisting of any two of them; the mass ratio of ethylene-methyl acrylate copolymer to benzotriazole compounds can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or a range consisting of any two of them; the mass ratio of diffuse reflection powder to benzotriazole compounds can be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or a range consisting of any two of them.
[0072] In actual operation, in the preparation of the first light-converting powder, part or all of the materials can be dispersed in a solvent according to actual selection, stirred and mixed, and then spray-dried.
[0073] In a specific embodiment of the present invention, the preparation of the first photoconversion powder includes:
[0074] S1: dissolving a benzotriazole compound in acetone to obtain a first solution;
[0075] S2: After mixing magnesium oxide and ethylene-methyl acrylate copolymer, disperse them in acetone, then add diffuse reflection powder, stir at 25-35°C for more than 2 hours, then add the first solution prepared in step S1, stir at room temperature for more than 1 hour, and spray dry.
[0076] The amount of acetone is not limited, and the main purpose is to ensure the uniformity of the mixing of the materials and the spray drying properties. For example, in step S1, the ratio of the amount of benzotriazole compound to acetone can be 1g﹕6.25mL, that is, for every 1g of benzotriazole compound, the amount of acetone is 6.25mL, but it is not limited to this. For example, in step S2, the ratio of the amount of magnesium oxide and ethylene-methyl acrylate copolymer to acetone can be 1g﹕5mL, that is, for every 1g of the mixture, the amount of acetone is 5mL, but it is not limited to this.
[0077] In a specific embodiment of the present invention, the second light conversion powder is mainly made of fluorescent powder, benzotriazole compound, magnesium oxide, ethylene-methyl acrylate copolymer and diffuse reflection powder in a mass ratio of (1.1-1.3) : 1 : (0.5-0.8) : (1.5-2) : (0.6-1).
[0078] By compounding the above substances in the second light conversion powder, the diffuse reflection of the converted light can be improved while ensuring the conversion of ultraviolet light.
[0079] For example, in different embodiments, in the second light conversion powder, the mass ratio of the phosphor to the benzotriazole compound can be 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1 or a range consisting of any two thereof; the mass ratio of magnesium oxide to the benzotriazole compound can be 0.5:1, 0.6:1, 0.7:1, 0.8:1 or a range consisting of any two thereof. ; The mass ratio of ethylene-methyl acrylate copolymer to benzotriazole compounds can be 1.5﹕1, 1.6﹕1, 1.7﹕1, 1.8﹕1, 1.9﹕1, 2﹕1 or a range of any two thereof; the mass ratio of diffuse reflective powder to benzotriazole compounds can be 0.6﹕1, 0.7﹕1, 0.8﹕1, 0.9﹕1, 1﹕1 or a range of any two thereof.
[0080] In actual operation, in the preparation of the second light conversion powder, part or all of the materials can be dispersed in a solvent according to actual selection, stirred and mixed, and then spray-dried.
[0081] In a specific embodiment of the present invention, the preparation of the second photoconversion powder includes:
[0082] S1: dissolving a benzotriazole compound in acetone to obtain a first solution;
[0083] S2: After mixing magnesium oxide and ethylene-methyl acrylate copolymer, disperse them in acetone, then add diffuse reflection powder, stir at 25-35°C for more than 2 hours, then add fluorescent powder, mix well, add the first solution prepared in step S1, stir at room temperature for more than 1 hour, and spray dry.
[0084] In the preparation of the second photoconversion powder, the amount of acetone is not limited, and the main purpose is to ensure the uniformity of the mixing of the materials and the spray drying. The specific amount can refer to the amount of solvent in the first photoconversion powder, but is not limited thereto.
[0085] In a specific embodiment of the present invention, the phosphor includes sodium yttrium tungstate crystals.
[0086] The present invention specifically lists a method for preparing a phosphor, but is not limited thereto. Sodium yttrium tungstate crystals prepared by conventional methods may also be used. The method for preparing the phosphor of the present invention includes:
[0087] The yttrium nitrate aqueous solution and the sodium tungstate aqueous solution are mixed to cause a precipitation reaction, and after continuous stirring for 25 to 120 minutes, they are heated to 95 to 100° C. and evaporated to dryness, and after washing with anhydrous ethanol, the solid material is collected; the solid material is sintered at a high temperature, and then crystals are grown in a micro-pull-down crystal growth furnace;
[0088] The concentration of the yttrium nitrate aqueous solution is 1.4-1.6 mol / L, and the concentration of the sodium tungstate aqueous solution is 0.8-1.2 mol / L; in the yttrium nitrate aqueous solution and the sodium tungstate aqueous solution, the molar ratio of yttrium nitrate to sodium tungstate is 3:2.
[0089] In a specific embodiment of the present invention, in the high temperature sintering, the sintering temperature is 750-850° C., and the sintering time is 4-8 hours.
[0090] In a specific embodiment of the present invention, the crystal growth in the micro-pull-down crystal growth furnace includes: placing at 500° C. for 8 hours.
[0091] In a specific embodiment of the present invention, yttrium nitrate crystals are used to prepare an aqueous yttrium nitrate solution; the preparation of yttrium nitrate crystals includes: irradiating yttrium oxide with 340-375nm ultraviolet light for more than 72h, then wetting yttrium oxide with water and hydrogen peroxide, then adding nitric acid solution, sealing and reacting at 100-200°C for 4-6h, and obtaining yttrium nitrate crystals after removing impurities.
[0092] In a specific embodiment of the present invention, in the preparation of yttrium nitrate crystals, the ratio of yttrium oxide, water, and hydrogen peroxide can be 10g﹕1mL﹕1mL, that is, for every 10g of yttrium oxide, the amount of water and hydrogen peroxide is 1mL and 1mL respectively. The ratio of yttrium oxide and nitric acid solution can be 10g﹕6mL, that is, for every 10g of yttrium oxide, the amount of nitric acid solution is 6mL. The concentration of the nitric acid solution can be 1.5-2mol / L.
[0093] For example, in different embodiments, the temperature of the sealing reaction can be 100°C, 120°C, 150°C, 180°C, 200°C or a range consisting of any two of them; the time of the sealing reaction can be 4h, 5h, 6h, etc.
[0094] In actual operation, impurity removal can be carried out according to the conventional operation of yttrium nitrate preparation. For example, the material after the sealed reaction can be filtered, the filtrate can be collected, cooled and crystallized, and the crystals can be collected. After the yttrium nitrate aqueous solution is prepared, polyacrylamide (molecular weight: 173.210) of about 0.3wt% of the nitrate dosage can be further added thereto, mixed and stirred, filtered, and the filtrate can be collected.
[0095] In a specific embodiment of the present invention, the structural formula of the benzotriazole compound is as follows:
[0096]
[0097] In a specific embodiment of the present invention, the diffuse reflection layer 3 is mainly prepared by weight portions of 100 parts of a third base resin, 0.3 to 0.9 parts of an initiator, 0.1 to 5 parts of a silane coupling agent, 0.6 to 1 parts of an acrylate monomer, 0.1 to 0.15 parts of an antioxidant, 0.05 to 0.09 parts of a light stabilizer and 10 to 15 parts of a diffuse reflection powder.
[0098] For example, in different embodiments, in the diffuse reflection layer 3, by weight, compared to 100 parts of the third matrix resin, the amounts of the remaining components may be as follows:
[0099] The amount of the initiator can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.9 parts or a range consisting of any two of them;
[0100] The amount of the silane coupling agent can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or a range consisting of any two of them;
[0101] The amount of the acrylic acid ester monomer can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part or a range consisting of any two of them;
[0102] The amount of the antioxidant can be 0.1 part, 0.11 part, 0.12 part, 0.13 part, 0.14 part, 0.15 part or a range consisting of any two of them;
[0103] The amount of the light stabilizer can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or a range consisting of any two of them;
[0104] The amount of diffuse reflective powder used can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or a range consisting of any two of them.
[0105] The diffuse reflection layer 3 of the present invention further has the effects of anti-reflection and diffuse reflection, and can realize the maximum transmission and utilization of the blue-green light of the first light conversion layer 1 and the second light conversion layer 2. In addition, the mixing of blue-green light can effectively reduce the light pollution generated when the adhesive film is applied to the BIPV module.
[0106] In a specific embodiment of the present invention, the light-guiding layer 4 is mainly prepared by weight portions of 75-85 parts of a fourth matrix resin, 0.3-0.9 parts of an initiator, 15-25 parts of a light-guiding masterbatch, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer and 8-16 parts of a diffuse reflection powder.
[0107] For example, in different embodiments, in the light guide layer 4, the amounts of the components in parts by weight may be as follows:
[0108] The amount of the fourth base resin can be 75 parts, 78 parts, 80 parts, 82 parts, 85 parts or a range consisting of any two of them;
[0109] The amount of the initiator can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.9 parts or a range consisting of any two of them;
[0110] The amount of the light-guiding masterbatch can be 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or a range consisting of any two of them;
[0111] The amount of the silane coupling agent can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts or a range consisting of any two of them;
[0112] The amount of the acrylic acid ester monomer can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part or a range consisting of any two of them;
[0113] The amount of the antioxidant can be 0.1 part, 0.11 part, 0.12 part, 0.13 part, 0.14 part, 0.15 part or a range consisting of any two of them;
[0114] The amount of the light stabilizer can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or a range consisting of any two of them;
[0115] The amount of diffuse reflective powder used can be 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or a range consisting of any two of them.
[0116] Figure 2 A schematic diagram of the longitudinal section of the diffuse reflection layer and the light guide layer provided in an embodiment of the present invention. It can be seen from the figure that the longitudinal section of the light guide layer 4 of the present invention includes a plurality of isosceles triangles evenly arranged in the horizontal direction;
[0117] The length a of the base and the height h of the isosceles triangle are 10-15 μm and 80-120 μm respectively; the distance L between the centers of adjacent isosceles triangles is 14-20 μm.
[0118] For example, in different embodiments, the length a of the base of the isosceles triangle can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or a range consisting of any two thereof; the height h of the isosceles triangle can be 80 μm, 90 μm, 100 μm, 110 μm, 120 μm or a range consisting of any two thereof; the distance L between the centers of adjacent isosceles triangles can be 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm or a range consisting of any two thereof.
[0119] In a specific embodiment of the present invention, the vertex of the isosceles triangle faces the diffuse reflection layer 3 .
[0120] The light-guiding layer 4 of the present invention can be designed with the size and spacing of the corresponding isosceles triangles according to the optimal fine grid line spacing in the battery design process, thereby increasing the diffuse reflection of light and effectively hiding the fine grid lines and welding wires, thereby improving the integration and aesthetics of the components and taking into account both the efficiency and aesthetics of the components.
[0121] The light-guiding layer 4 of the present invention is produced by extrusion through a die head having a certain structure, and the cross-sectional view of the die head corresponds to the longitudinal cross-sections of the diffuse reflection layer and the light-guiding layer. Figure 3 This is a schematic diagram of the structure of a single-module co-extrusion die head provided in an embodiment of the present invention. The longitudinal section of the co-extrusion die head for extruding the diffuse reflection layer 3 and the light guide layer 4 of the present invention includes a plurality of isosceles triangle modules evenly arranged in the horizontal direction. The structure of a single isosceles triangle module corresponds to the isosceles triangle of the light guide layer 4, and each isosceles triangle is a hollow structure; the outer space of the isosceles triangle corresponds to the extrusion channel of the diffuse reflection layer 3.
[0122] In a specific embodiment of the present invention, the first matrix resin and the second matrix resin each independently include at least one of ethylene-vinyl acetate copolymer and ethylene-acrylic acid copolymer. Further, in the first matrix resin and the second matrix, the mass ratio of the ethylene-vinyl acetate copolymer to the ethylene-acrylic acid copolymer is (3-5):1.
[0123] For example, in different embodiments, in the first matrix resin, the mass ratio of ethylene-vinyl acetate copolymer to ethylene-acrylic acid copolymer can be 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or a range consisting of any two of them.
[0124] In a specific embodiment of the present invention, the third matrix resin is ethylene-vinyl acetate copolymer. The third matrix resin has a certain refractive index and high transparency, and further improves the diffuse reflection effect by matching each layer structure.
[0125] In a specific embodiment of the present invention, the fourth matrix resin includes at least one of ethylene-vinyl acetate copolymer and ethylene-methyl acrylate copolymer. Further, in the fourth matrix resin, the mass ratio of the ethylene-vinyl acetate copolymer to the ethylene-methyl acrylate copolymer is (6-8):1.
[0126] For example, in different embodiments, in the fourth matrix resin, the mass ratio of ethylene-vinyl acetate copolymer to ethylene-methyl acrylate copolymer can be 6:1, 6.5:1, 7:1, 7.5:1, 8:1 or a range consisting of any two of them.
[0127] In a specific embodiment of the present invention, the light-guiding masterbatch is mainly made of a matrix and a diffuse reflective powder in a mass ratio of (3.5-4.5) : 1. Furthermore, the matrix is an ethylene-methyl acrylate copolymer.
[0128] For example, in different embodiments, the mass ratio of the matrix to the diffuse reflective powder in the light-guiding masterbatch can be 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1 or any two of them. The matrix and the diffuse reflective powder can be conventionally extruded and granulated in corresponding proportions.
[0129] In a specific embodiment of the present invention, in the optical transfer adhesive film, the thickness of the first optical transfer layer 1 is 130-150 μm, the thickness of the second optical transfer layer 2 is 110-130 μm, and the total thickness of the diffuse reflection layer 3 and the light guide layer 4 is 280-320 μm.
[0130] For example, in different embodiments, the thickness of the first light conversion layer 1 can be 130 μm, 135 μm, 140 μm, 145 μm, 150 μm or any two thereof; the thickness of the second light conversion layer 2 can be 110 μm, 115 μm, 120 μm, 125 μm, 130 μm or any two thereof; the common thickness of the diffuse reflection layer 3 and the light guide layer 4 can be 280 μm, 290 μm, 300 μm, 310 μm, 320 μm or any two thereof. The longitudinal section of the light guide layer 4 includes a plurality of isosceles triangles, that is, the light guide layer 4 includes a plurality of rib structures arranged in parallel and spaced apart, the diffuse reflection layer 3 has a groove structure matching the rib structure of the light guide layer 4, and the rib structure in the light guide layer 4 is filled in the groove structure of the diffuse reflection layer 3.
[0131] In the light transfer adhesive film of the present invention, the auxiliary agents used in each layer, such as initiator, silane coupling agent, acrylate monomer, antioxidant, light stabilizer, etc., can be selected conventionally, and are listed here, but not limited to:
[0132] The initiator may be a peroxide initiator, such as at least one of disuccinic acid peroxide, tert-butyl peracetate, tert-butyl peroxyisopropyl carbonate and tert-butyl perbenzoate;
[0133] The silane coupling agent can be 570 (Kaishida), O174S (Jianghan Chemical), J&Y3130 (Kaishida);
[0134] Acrylate monomers include but are not limited to polyethylene glycol (200) dimethacrylate, polyethylene glycol (400) dimethacrylate, polyethylene glycol (600) dimethacrylate, neopentyl glycol (2) PO diacrylate, polypropylene glycol (1000) EO (3) dimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate and neopentyl glycol diacrylate;
[0135] The antioxidant includes but is not limited to at least one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(4-nonylphenol) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris[2,4-di-tert-butylphenyl] phosphite and dioctadecyl pentaerythritol diphosphite;
[0136] The light stabilizer includes but is not limited to at least one of bis(1,2,2,6,6-pentamethylpiperidinol) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, diphenylaminourea and dimethyl azobisisobutyrate.
[0137] Another aspect of the present invention provides a method for preparing any one of the above-mentioned light transfer adhesive films, comprising the following steps:
[0138] (a) co-extruding the first light conversion layer and the second light conversion layer according to the raw material ratio to obtain a light conversion composite layer;
[0139] (b) co-extruding the diffuse reflection layer and the light guide layer according to the raw material ratio, and performing heat bonding treatment with the light conversion composite layer, and winding;
[0140] During the thermal bonding process, the second light conversion layer of the light conversion composite layer is bonded to the diffuse reflection layer.
[0141] In actual operation, the first light conversion layer and the second light conversion layer can be put into the extruder according to the raw material ratio in advance, and co-extruded at 50-100°C and 60-70r / min to be pulled into a film and then rolled up to obtain a light conversion composite layer; then the diffuse reflection layer and the light guide film layer can be put into the extruder according to the raw material ratio, and co-extruded at 50-100°C and 60-70r / min to be pulled into a film and then rolled up to obtain a light conversion composite layer; Figure 3 After co-extrusion by the co-extrusion die head shown, one side of the diffuse reflection layer and one side of the second light conversion layer of the light conversion composite layer are subjected to heat bonding treatment and then rolled up.
[0142] Another aspect of the present invention provides a photovoltaic module, comprising any one of the above-mentioned light transfer adhesive films.
[0143] Figure 4When the light transfer adhesive film of the present invention is used in photovoltaic modules, one side of the light guide layer 4 is attached to the battery cell 5, which can not only increase diffuse reflection, but also partially hide the grid lines of the module, improving the aesthetics of the module.
[0144] The light transfer adhesive film of the present invention has excellent bonding strength with glass and high transmittance. The photovoltaic module made by using the light transfer adhesive film of the present invention has low power attenuation after DH aging, no shadow in EL photos, etc., the diffuse reflectivity of the adhesive film reaches 40% to 57%, the power gain is greater than 2%, and the cutoff utilization rate of the adhesive film for ultraviolet rays reaches 90% to 97%.
[0145] Example 1
[0146] This embodiment provides a light transfer adhesive film, including a first light transfer layer, a second light transfer layer, a diffuse reflection layer and a light guide layer arranged in sequence. The thickness of the first light transfer layer is 140 μm, the thickness of the second light transfer layer is 120 μm, the common thickness of the diffuse reflection layer and the light guide layer is 300 μm, and the total thickness of the light transfer adhesive film is 560 μm. The longitudinal section of the light guide layer includes a plurality of isosceles triangles uniformly arranged in the horizontal direction; the base length a and height h of the isosceles triangle are 15 μm and 120 μm respectively; the distance L between the centers of adjacent isosceles triangles is 18 μm.
[0147] Among them, the raw materials of the first light conversion layer mainly include: 80 parts of EVA (V2806 / Sulbon Chemical), 20 parts of EAA (DowDuPont / 3150), 0.6 parts of peroxide (Changxing Chemical / TBEC), 0.6 parts of silane (570), 0.7 parts of acrylate monomer (GM66 / Guojing Chemical), 0.15 parts of antioxidant (Antioxidant 1010 / BASF), 0.06 parts of light stabilizer (UV-292 / Unaid) and 0.8 parts of the first light conversion powder.
[0148] Wherein, the preparation of the first light-converting powder includes:
[0149] (1) 80 g of a benzotriazole compound was dissolved in 500 mL of acetone to obtain a solution A; wherein the structural formula of the benzotriazole compound is as follows:
[0150]
[0151] (2) MgO with an average particle diameter of ≤0.2 μm was dried and mixed with EMA powder (Arkema / 29MA03) at a mass ratio of 1:3 to obtain a mixed powder. 200 g of the mixed powder was dispersed in 1000 mL of acetone, and then 70 g of diffuse reflectance powder (Dow Corning / DOWSIL 30-424) was added and stirred at 30° C. for 2 h. Then, solution A obtained in step (1) was added thereto, and the mixture was stirred at room temperature for 1 h and then spray-dried through an atomizing nozzle of about 1 μm to obtain the corresponding first light conversion powder.
[0152] The raw materials of the second light conversion layer mainly include: 80 parts of EVA (V2806 / Sulbon Chemical), 20 parts of EAA (DowDuPont / 3150), 0.4 parts of peroxide (Zhenghua Chemical / TBPIN), 0.6 parts of silane (570), 0.7 parts of acrylate monomer (GM66 / Guojing Chemical), 0.15 parts of antioxidant (Antioxidant 1010 / BASF), 0.06 parts of light stabilizer (UV-292 / Unaide) and 0.8 parts of second light conversion powder.
[0153] Wherein, the preparation of the second light conversion powder includes:
[0154] (1) irradiating yttrium oxide with 340-375 nm ultraviolet light for 72 h to activate it, then taking 50 g of the activated yttrium oxide and wetting it with 5 mL of water and 5 mL of hydrogen peroxide, then adding 30 mL of 2 mol / L nitric acid aqueous solution, sealing it, and heating it to 150° C. to react for 5 h; cooling after the reaction, filtering and collecting the filtrate, and then cooling and crystallizing to collect yttrium nitrate crystals; dissolving the yttrium nitrate crystals in water to prepare an yttrium nitrate aqueous solution with a concentration of 1.5 mol / L, then adding 0.3 wt% of polyacrylamide to the mass of the yttrium nitrate crystals, mixing and stirring, filtering, and collecting the filtrate, i.e., the yttrium nitrate aqueous solution.
[0155] (2) Add 1 mol / L sodium tungstate solution to the yttrium nitrate aqueous solution obtained in step (1) to cause precipitation reaction, and continue stirring for 60 minutes; then heat at 100°C until the liquid is evaporated, and then wash it with 500 mL of anhydrous ethanol for 4 times, collect the solid material and transfer it to a crucible, place it in a muffle furnace, and sinter it at 800°C for 6 hours; after sintering, place it in a micro-pull-down crystal growth furnace at 500°C for 8 hours to achieve the growth of sodium yttrium tungstate crystals. Wherein, the molar ratio of yttrium nitrate to sodium tungstate is 3:2.
[0156] (3) 80 g of a benzotriazole compound was dissolved in 500 mL of acetone to obtain a solution A; wherein the structural formula of the benzotriazole compound is as follows:
[0157]
[0158] (4) MgO with an average particle diameter of ≤0.2 μm was dried and mixed with EMA powder (Arkema / 29MA03) at a mass ratio of 1:3 to obtain a mixed powder. 200 g of the mixed powder was dispersed in 1000 mL of acetone, and then 70 g of diffuse reflectance powder (Dow Corning / DOWSIL 30-424) was added and stirred at 30° C. for 2 h. 96 g of sodium yttrium tungstate crystals obtained in step (2) were added and mixed and stirred evenly. Then, solution A obtained in step (3) was added thereto. After stirring at room temperature for 1 h, the mixture was spray-dried through an atomizing nozzle of about 1 μm to obtain the corresponding second light conversion powder.
[0159] The main raw materials of the diffuse reflection layer include: 100 parts of EVA (V2806 / Sulbon Chemical), 0.6 parts of peroxide (Zhenghua Chemical / TBEC), 0.5 parts of silane (570), 0.8 parts of acrylate monomer (GM66 / Guojing Chemical), 0.1 parts of antioxidant (Antioxidant 1010 / BASF), 0.07 parts of light stabilizer (UV-292 / Unaide) and 12 parts of diffuse reflection powder (Dow Corning / DOWSIL 30-424) by weight.
[0160] The main raw materials of the light-guiding layer include: 70 parts by weight of EVA (V2806 / Sulbon Chemical), 10 parts of EMA (X8990 / SK Chemical), 20 parts of light-guiding masterbatch, 0.6 parts of peroxide (Zhenghua Chemical / TBEC), 0.7 parts of silane (570), 1 part of acrylate monomer (GM66 / Guojing Chemical), 0.1 parts of antioxidant (Antioxidant 1010 / BASF), 0.09 parts of light stabilizer (UV-292 / Unaide) and 16 parts of diffuse reflective powder (Dow Corning / DOWSIL 30-424).
[0161] Among them, the light-guiding masterbatch is made by conventional granulation of EMA (X8990 / SK Chemical) and diffuse reflective powder (Dow Corning / DOWSIL 30-424) in a mass ratio of 4:1.
[0162] The method for preparing the optical transfer adhesive film of this embodiment comprises the following steps:
[0163] (1) The raw materials of the first light conversion layer and the second light conversion layer are respectively put into two screws according to the raw material ratio, and extruded and rolled by a cast extruder to obtain a light conversion composite layer; wherein the first to ninth temperature zones of the screw are 50° C., 60° C., 65° C., 70° C., 70° C., 75° C., 75° C., 75° C., respectively, the screw speed is 60 r / min, and the die head temperature is 75-80° C.;
[0164] (2) According to the raw material ratio of diffuse reflection layer and light guide layer, Figure 3The co-extrusion die shown in the figure performs cast extrusion (wherein, the first to ninth temperature zones of the screw are 55°C, 65°C, 70°C, 75°C, 75°C, 75°C, 80°C, 80°C, 80°C, respectively, the screw speed is 60r / min, and the die temperature is 75-80°C), and one side of the diffuse reflection layer and one side of the second light conversion layer of the light conversion composite layer obtained in step (1) are pressed together by a steel roller and a rubber roller for heat bonding treatment, the temperature of the two rollers is maintained at 45°C, and the film is rolled up to obtain a light conversion adhesive film with an overall thickness of 560μm.
[0165] Example 2
[0166] This embodiment refers to the optical transfer adhesive film and preparation method thereof of Embodiment 1, with the only difference being that the amount of the first optical transfer powder in the first optical transfer layer is different; and the amount of the second optical transfer powder in the second optical transfer layer is different.
[0167] In this embodiment, the usage of the first light-converting powder is 0.3 parts, and the usage of the second light-converting powder is 0.3 parts.
[0168] Example 3
[0169] This embodiment refers to the optical transfer adhesive film and preparation method thereof of Embodiment 1, with the only difference being that the amount of the first optical transfer powder in the first optical transfer layer is different; and the amount of the second optical transfer powder in the second optical transfer layer is different.
[0170] In this embodiment, the amount of the first light-converting powder is 0.5 parts, and the amount of the second light-converting powder is 0.5 parts.
[0171] Example 4
[0172] This embodiment refers to the light transfer adhesive film and preparation method thereof of Embodiment 1, and the only difference is that the structures of the diffuse reflection layer and the light guide layer are different.
[0173] The diffuse reflection layer and the light guide layer in this embodiment are obtained by co-extrusion through a conventional die. The longitudinal sections of the two layers are both rectangular. The thicknesses of the diffuse reflection layer and the light guide layer are 180 μm and 120 μm, respectively.
[0174] Example 5
[0175] This embodiment refers to the optical transfer adhesive film and preparation method thereof of Embodiment 1, with the only difference being that in the preparation method of the first optical transfer powder, the amount of the mixed powder used in step (2) is different.
[0176] In the preparation of the first photoconversion powder of this embodiment, the amount of the mixed powder used in step (2) is 100 g.
[0177] Example 6
[0178] This embodiment refers to the optical transfer adhesive film and preparation method thereof of Embodiment 1, with the only difference being that in the preparation method of the second optical transfer powder, the amount of the mixed powder used in step (4) is different.
[0179] In the preparation of the second photoconversion powder of this embodiment, the amount of the mixed powder used in step (4) is 100 g.
[0180] Example 7
[0181] This embodiment refers to the light transfer adhesive film and its preparation method of Example 1, with the only difference being that in the preparation method of the first light transfer powder, in step (2), diffuse reflection powder is not included; and 0.2 parts by weight of diffuse reflection powder (Dow Corning / DOWSIL 30-424PC light diffuser) is added to the raw materials of the first light transfer layer.
[0182] Comparative Example 1
[0183] Comparative Example 1 refers to the optical transfer adhesive film and preparation method thereof of Example 1, except that: in the first optical transfer layer, the amount of the first optical transfer powder is different; in the second optical transfer layer, the amount of the second optical transfer powder is different.
[0184] In Comparative Example 1, the amount of the first photoconversion powder used was 0.1 parts, and the amount of the second photoconversion powder used was 0.1 parts.
[0185] Comparative Example 2
[0186] Comparative Example 2 refers to the photoconversion adhesive film and preparation method thereof of Example 1, except that: in the first photoconversion layer, the amount of the first photoconversion powder is different; in the second photoconversion layer, the amount of the second photoconversion powder is different.
[0187] In Comparative Example 2, the amount of the first light-converting powder used is 1.5 parts, and the amount of the second light-converting powder used is 1.5 parts.
[0188] Comparative Example 3
[0189] Comparative Example 3 refers to the light-converting adhesive film and its preparation method of Example 1, except that: no diffuse reflection layer and light-guiding layer are included, that is, it corresponds to the light-converting composite layer structure prepared in Example 1.
[0190] Experimental example
[0191] In order to compare and illustrate the performance differences of different optical transfer adhesive films, the initial light transmittance, light transmittance after aging (ultraviolet aging, irradiation dose UV120kwh), ultraviolet light utilization rate and diffuse reflectivity of different optical transfer adhesive films were tested; at the same time, the optical transfer adhesive films of different embodiments and comparative examples were used, matched with 2200mm×11125mm, 2mm thick tempered glass (Amaden), 210mm HJT battery (Anhui Huasheng), welding strip and bus bar (Talisong), laminated at 145°C, evacuation time 360s, and lamination time 800s to obtain components, and the initial bonding force of the components (bonding force between the film and the back glass) and the power attenuation after DH2000h were tested. The test results are shown in Table 1.
[0192] Among them, the initial bonding force and DH2000h module power were tested according to GB / T 29848-2018; the diffuse reflectance was tested using an OL740-70 spectrophotometer, the ultraviolet light utilization was calculated using the following formula, and the transmittance was tested using Shimadzu's UV2600.
[0193] UV light utilization test method and calculation formula:
[0194] The UV cutoff rate of the entire film was measured by Shimadzu UV2600 and recorded as T m ; Horiba was used to test the blue light quantum efficiency and green light quantum efficiency of the film, which were recorded as Q1 and Q2 respectively; Shimadzu UV2600 was used to test the UV cutoff rates of the first light conversion layer and the second light conversion layer (two layers of film were prepared separately), which were recorded as T1 and T2 respectively; the calculation formula of the UV utilization rate Q is as follows:
[0195]
[0196] Specifically, it is determined by the film's ability to cut off ultraviolet light and the proportion of blue light and green light converted by the film.
[0197] Table 1 Performance test results of different photosensitive adhesive films
[0198]
[0199] According to the above test results, the light-converting adhesive film of the present invention can convert ultraviolet light into blue light and green light through a multi-layer structure, and improve the diffuse reflection of the converted blue light and green light. At the same time, by cooperating with the diffuse reflection layer and the light-guiding layer, the transmittance and utilization rate of the converted blue-green light can be improved, thereby improving the power gain of the overall component.
[0200] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A light transfer adhesive film, characterized in that: It includes a first light conversion layer, a second light conversion layer, a diffuse reflection layer and a light guide layer which are arranged in sequence; The first light conversion layer is mainly made of 100 parts by weight of a first base resin, 0.3-0.9 parts of an initiator, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer, and 0.3-0.8 parts of a first light conversion powder; The second light conversion layer is mainly made of 100 parts by weight of a second base resin, 0.3-0.7 parts of an initiator, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer, and 0.3-0.8 parts of a second light conversion powder; The first light conversion powder receives light with a wavelength of 280 to 320 nm and converts it to generate blue light; the second light conversion powder receives light with a wavelength of 320 to 400 nm and converts it to generate green light.
2. The optical transfer adhesive film according to claim 1, characterized in that: The first light conversion powder is mainly made of benzotriazole compounds, magnesium oxide, ethylene-methyl acrylate copolymer and diffuse reflection powder in a mass ratio of 1:(0.5-0.8):(1.5-2):(0.6-1); The second light conversion powder is mainly made of fluorescent powder, benzotriazole compound, magnesium oxide, ethylene-methyl acrylate copolymer and diffuse reflection powder in a mass ratio of (1.1-1.3) ﹕ 1 ﹕ (0.5-0.8) ﹕ (1.5-2) ﹕ (0.6-1); Preferably, the structural formula of the benzotriazole compound is as follows:
3. The optical transfer adhesive film according to claim 2, characterized in that: The phosphor includes sodium yttrium tungstate crystals.
4. The optical transfer adhesive film according to claim 1, characterized in that: The diffuse reflection layer is mainly prepared from 100 parts of a third base resin, 0.3-0.9 parts of an initiator, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer and 10-15 parts of a diffuse reflection powder, in parts by weight.
5. The optical transfer adhesive film according to claim 1, characterized in that: The light-guiding layer is mainly prepared by weight portions of 75-85 parts of a fourth matrix resin, 0.3-0.9 parts of an initiator, 15-25 parts of a light-guiding masterbatch, 0.1-5 parts of a silane coupling agent, 0.6-1 parts of an acrylate monomer, 0.1-0.15 parts of an antioxidant, 0.05-0.09 parts of a light stabilizer and 8-16 parts of a diffuse reflection powder.
6. The optical transfer adhesive film according to claim 1, characterized in that: The longitudinal section of the light guide layer includes a plurality of isosceles triangles evenly arranged in the horizontal direction; The base length and height of the isosceles triangle are 10-15 μm and 80-120 μm respectively; the distance between the centers of adjacent isosceles triangles is 14-20 μm; Preferably, the vertex of the isosceles triangle faces the diffuse reflection layer.
7. The optical transfer adhesive film according to claim 5, characterized in that: The light-guiding masterbatch is mainly made of a matrix and diffuse reflective powder in a mass ratio of (3.5-4.5) : 1; Preferably, the matrix is ethylene-methyl acrylate copolymer.
8. The optical transfer adhesive film according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The thickness of the first light conversion layer is 130-150 μm; (2) The thickness of the second light conversion layer is 110 to 130 μm; (3) The combined thickness of the diffuse reflection layer and the light guide layer is 280 to 320 μm.
9. The method for preparing the light transfer adhesive film according to any one of claims 1 to 8, characterized in that: The steps include: (a) co-extruding the first light conversion layer and the second light conversion layer according to the raw material ratio to obtain a light conversion composite layer; (b) co-extruding the diffuse reflection layer and the light guide layer according to the raw material ratio, and performing heat bonding treatment with the light conversion composite layer, and winding; During the thermal bonding process, the second light conversion layer of the light conversion composite layer is bonded to the diffuse reflection layer.
10. A photovoltaic module, characterized in that The invention comprises the light transfer adhesive film according to any one of claims 1 to 8 or the light transfer adhesive film prepared by the preparation method according to claim 9.
